Population dynamics of bronze beetle Eucolaspis spp (Coleoptera Chrysomelidae) in relation to other soil macroinvertebrates in organic apple orchards in Hawkes Bay - Doddala, P.R.C.; Minor, M.A.; Rogers, D.J. (New Zealand Plant Protection, 2010)
The population structure and dynamics of bronze beetle Eucolaspis spp and other soil macroinvertebrates were studied in eight organic apple orchards in Hawkes Bay during spring/summer 200708 Orchards with high bronze beetle population densities also had higher abundance of all types of soil macroinvertebrates than orchards with low bronze beetle populations Surfacedwelling generalist predators were more numerous (on average 536 versus 405 predators per trap) in orchards with low bronze beetle density than in orchards with high beetle density This result was mainly due to spider numbers in pitfall traps which were highest during January It may be that within orchards where surface dwelling spiders are most abundant these spiders may be predating upon newly emergent adult bronze beetles as they move from the soil to the apple foliage